2005
DOI: 10.1002/ijc.21166
|View full text |Cite
|
Sign up to set email alerts
|

Mantle cell lymphomas with low levels of cyclin D1 long mRNA transcripts are highly proliferative and can be discriminated by elevated cyclin A2 and cyclin B1

Abstract: The role of transcript variants of cyclin D1 in cancer biology is unclear. Most tumors with high levels of cyclin D1 express 2 transcripts due to alternative splicing: one full-length transcript of 4.4 kb and one short transcript of approximately 1.7 kb. The short transcript lacks part of the 3 0 UTR region regulating mRNA stability and has a longer half-life. In our study, the contribution of each of these mRNAs to gene expression and cell proliferation has been investigated in mantle cell lymphoma (MCL), a B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 34 publications
1
24
0
Order By: Relevance
“…In support of this hypothesis, the loss of the cyclin D1 3'UTR has been linked to hyper-proliferative forms of MCL. 18 A number of studies have hypothesized that AREs in the 3'UTR could potentially destabilize the cyclin D1 3'UTR and therefore their loss could contribute to enhanced stability and overexpression of cyclin D1 protein. Using a sensitive reporter assay, the deletion of the AREs in the cyclin D1 3'UTR actually leads to a marked reduction in reporter activity suggesting that AREs have a stabilizing function on the cyclin D1 mRNA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In support of this hypothesis, the loss of the cyclin D1 3'UTR has been linked to hyper-proliferative forms of MCL. 18 A number of studies have hypothesized that AREs in the 3'UTR could potentially destabilize the cyclin D1 3'UTR and therefore their loss could contribute to enhanced stability and overexpression of cyclin D1 protein. Using a sensitive reporter assay, the deletion of the AREs in the cyclin D1 3'UTR actually leads to a marked reduction in reporter activity suggesting that AREs have a stabilizing function on the cyclin D1 mRNA.…”
Section: Discussionmentioning
confidence: 99%
“…17 Hyper-proliferative forms of MCL are characterised by high levels of cyclin D1, especially a shorter transcript which has been associated with a poor prognosis. 18 These shorter forms of cyclin D1 in MCL were believed to derive from an alternatively splicing event which generates a shorter isoform of the cyclin D1 gene. However, in a number of MCL patients, it has recently been demonstrated that the shorter isoforms of the cyclin D1 gene in MCL result from genomic deletions or point mutations that prematurely truncate the cyclin D1 3'UTR.…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of chromosomal abnormalities has revealed that the ORP3 (OSBPL3 -HGNC database) gene region in chromosome 7 is often gained and overexpressed in colon tumors and osteosarcoma (Ozaki et al, 2003;Staub et al, 2006;Tsafrir et al, 2006). Increased expression of ORP3 mRNA has frequently been reported in B-cell-associated malignancies (Ando et al, 2003;Sander et al, 2005;Chng et al, 2006;Ek et al, 2006) and testicular cancer (Sperger et al, 2003;Yamada et al, 2004;Almstrup et al, 2005;Gashaw et al, 2005;Juric et al, 2005). In a prospective study of patients with diffuse large B-cell lymphoma (DLBCL), high ORP3 expression was associated with increased mortality (Ando et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…With regard to MCL, the 'Lymphoma and Leukemia Molecular Profiling Project (LLMPP)' demonstrated that the length of survival of MCL patients depends upon quantitative differences in progression from G1/S phase of the cell cycle (17). Sander et al also showed that a subset of MCL tumors with low levels of the long CCND1 transcript is highly proliferative and some of its related genes have homology to the group of cell cycle (G1/S) promoting E2F transcription partners (18). Indeed, there is a strong correlation between these reported genes and the 60 we identified in this study as involved in transformation (Table III), which emphasizes the importance of G1/S regulators in MCL evolution.…”
Section: Discussionmentioning
confidence: 99%